Relationship between the magnetic susceptibility and lithological composition in sediment cores from lakes of Matița-Merhei Depression (Danube Delta, Romania): towards a proxy method of sedimentological and enviromental fingerprinting. (Geo-Eco-Marina, 2014)
In the framework of the Danube Delta geosystem spatial evolution study, new results achieved for sediment cores − this time collected from the Matiţa − Merhei Depression lakes − are added up to the data which were previously published with regard to the Meşteru − Fortuna Depression. Actually, it is the second part of the series of papers dedicated to the magneto − lithological investigation of sediment columns, taken out from various aquatic environments, in both the Fluvial and Marine Delta Plains. Vertical profiles of magnetic susceptibility (MS) and contents of siliciclastic/minerogenic/detrital fraction (SIL), total organic matter (TOM) and carbonate (CAR) are carried out for 9 cores (not longer than 55.5 cm), collected from four lakes (Babina, Matiţa, Polideanca and Bogdaproste), a swamp (Polideanca − Lopatna) and a canal (Lopatna − Polideanca). These records are based on MS (k) measurements (with a Kappabridge KLY-2), and respectively, on lithological component contents analyses (by the “Loss on Ignition”/LOI method), performed on sediment samples obtained by core slicing, at 1-3 cm intervals. MS, SIL, TOM and CAR maps are carried out for surficial sediments, as well, in order to describe the magneto-lithological background which characterizes each of the lakes from where the short sediment cores were extracted. The MS calibration of the lake sediments (core and grab samples) is carried out by using a k scale with 5 classes. The correlation coefficient (r) is calculated for all 6 possible pairs of above specified parameters (SIL vs. k, TOM vs. k, CAR vs. k, SIL vs. TOM, SIL vs. CAR and TOM vs. CAR). To evaluate the correlation size, a scale with 6 steps is used. Positive/direct and negative/reversed correlations have always been obtained for SIL vs. k, and TOM vs. k, respectively. Therefore, new proofs are added to assign the magnetic parameter proxy quality as environmental and sedimentological fingerprinting tool. Another important result of the present study is the detection of some marine clays located very close below the water/sediment interface, intercepted, particularly, at the lower/basal part of two cores from the Babina Lake, two from Matiţa Lake, and another one from the Lopatna − Polideanca Canal. These marine deposits (with macroscopically identified specific fauna) are characterized by clearly different magnetic and lithological signatures (high MS values and SIL contents, low TOM contents), as compared with the fingerprints recovered from the overlying muds (sampled at the upper part of the cores). The presence of a marine episode revealed by some of the sediment cores collected from lakes of the Matiţa − Merhei Depression, which is a part of the Fluvial Delta Plain, is very interesting and can represent a contribution to the better knowledge of the deltaic system temporal and spatial evolution.
Keywords: environmental magnetism; minerogenic/siliciclastic component; total organic matter component; carbonate component; lake sediments; marine clays